Evaluation of acute and sub-acute toxicity of Ethanolic dry fruit extract of crataegus Oxycantha l. In male wistar rats - KUMARASWAMY D,; JAMUNA RANI R,; ALWIN D,; KIRAN B,; BALAJI R, (International Journal of Pharma and Bio Sciences, 2016)
Crataegus oxycantha popularly known as Hawthorn is widely distributed in northern hemisphere especially in Asia, Europe and parts of America. Howthorn consist of more than 200 species and several parts of the plant is traditionally used in the china and Europe. In India it is widely distributed in the temperate Himalayan regions and the different parts of plant is used for multiple health effects like hypolipidaemic, hypotensive and anti-atherosclerotic purposes due to its active phytochemical properties. This species C. Oxycantha has not been adequately studied and the histopathological changes for its toxicity and safe use have not been established. Thus The aim of the present study was to evaluate acute and sub-acute toxicity of the ethanolic dry Fruit powder extract of Crataegus Oxycantha (coc) on male wistar rats at different dose levels of 100, 200, 500, 1000, and 2000mg/kg b.w.) At a rate of 1.0ml /rat/day to different sets of animals for 30 days. Results from the present study have elucidated that treatment of C.Oxycantha exerts no significant signs of toxicity at any dose level when compared with the control group used in the study. Behavioural, Biochemical as well as haematological parameters were unaltered throughout the study. Histopathological sections of different organs have no signs of tissue damage or necrosis. The results of the study have suggested there was no obvious toxicity observed with the treatment of C.Oxycantha fruit powder extract and this preclinical toxicological evaluation strongly supports our further studies on various cardiovascular abnormalities.